2020
DOI: 10.1111/cxo.12943
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral refraction and higher order aberrations

Abstract: Peripheral image quality influences several aspects of human vision. Apart from off‐axis visual functions, the manipulation of peripheral optical errors is widely used in myopia control interventions. This, together with recent technological advancements enabling the measurement of peripheral errors, has inspired many studies concerning off‐axis optical aberrations. However, direct comparison between these studies is often not straightforward. To enable between‐study comparisons and to summarise the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Further studies that quantify the accommodation response using objective automated techniques while controlling for pupil diameter are still required to understand if ortho-k significantly alters the accommodation response in children and adults, and if this contributes to the myopia control effect of ortho-k. Since measurements of peripheral refraction [338,339], HOAs [340], and the accommodation response [331] can vary with pupil size, several studies have investigated the relationship between pupil size and axial eye growth in children managed with ortho-k. In addition to the empirical data summarised in Table 5, based on theoretical modelling, a larger pupil diameter yields more positive primary spherical aberration and relative peripheral myopic defocus following ortho-k treatment [322].…”
Section: Accommodationmentioning
confidence: 99%
“…Further studies that quantify the accommodation response using objective automated techniques while controlling for pupil diameter are still required to understand if ortho-k significantly alters the accommodation response in children and adults, and if this contributes to the myopia control effect of ortho-k. Since measurements of peripheral refraction [338,339], HOAs [340], and the accommodation response [331] can vary with pupil size, several studies have investigated the relationship between pupil size and axial eye growth in children managed with ortho-k. In addition to the empirical data summarised in Table 5, based on theoretical modelling, a larger pupil diameter yields more positive primary spherical aberration and relative peripheral myopic defocus following ortho-k treatment [322].…”
Section: Accommodationmentioning
confidence: 99%
“…Some previous studies found no correlation between foveal HOA and refractive error, whereas others report a correlation between HOA and myopia . Additionally, in a recent review on peripheral optical errors, myopes had slightly worse image quality than emmetropes in the 20° visual field . Further studies with larger sample size are needed to see whether myopes are less symmetric than emmetropes in their sensitivity to peripheral defocus.…”
Section: Discussionmentioning
confidence: 89%
“…33 Peripheral vision is compromised not only because of low cone density and limited ganglion cell density, 34 but also for increased optical aberrations at the peripheral retina. 17,35,36 Development of myopic refractive error is mainly related to an increase in axial length (AL), following a rule-of-thumb that every 300 microns AL growth causes one diopter rise in myopia, considering no alteration of other ocular components. 37,38 However, the AL growth is unlikely to always con ned at the macular area but extends to an unknown area at the posterior ocular wall.…”
Section: Discussionmentioning
confidence: 99%